Stable isotope analysis of vertebrae reveals ontogenetic changes in habitat in an endothermic pelagic shark - Carlisle, Aaron B. (Proc Biol Sci, 2015)
Ontogenetic changes in habitat are driven by shifting life-history requirements and play an important role in population dynamics. However, large portions of the life history of many pelagic species are still poorly understood or unknown. We used a novel combination of stable isotope analysis of vertebral annuli, Bayesian mixing models, isoscapes and electronic tag data to reconstruct ontogenetic patterns of habitat and resource use in a pelagic apex predator, the salmon shark (Lamna ditropis). Results identified the North Pacific Transition Zone as the major nursery area for salmon sharks and revealed an ontogenetic shift around the age of maturity from oceanic to increased use of neritic habitats. The nursery habitat may reflect trade-offs between prey availability, predation pressure and thermal constraints on juvenile endothermic sharks. The ontogenetic shift in habitat coincided with a reduction of isotopic niche, possibly reflecting specialization upon particular prey or habitats. Using tagging data to inform Bayesian isotopic mixing models revealed that adult sharks primarily use neritic habitats of Alaska yet receive a trophic subsidy from oceanic habitats. Integrating the multiple methods used here provides a powerful approach to retrospectively study the ecology and life history of migratory species throughout their ontogeny.